2010
DOI: 10.1080/03075070903348396
|View full text |Cite
|
Sign up to set email alerts
|

Giving thanks: the relational context of gratitude in postgraduate supervision

Abstract: Successful postgraduate supervision is often dependent upon the quality of the relationship between postgraduates and their supervisors. This article reports on two studies that focus on grateful affect and grateful expression within low-and high-trust postgraduate-supervisor working relationships. In Study 1, a sample of Canadian postgraduates and supervisors was interviewed to explore the consequences of expressed gratitude and identify supervisory behaviors for which postgraduates are grateful. In Study 2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 45 publications
1
7
0
3
Order By: Relevance
“…The relationship between the benefactor and the beneficiary has influence over gratitude. Unsworth, Turner, Williams, and Piccin-Houle (2010) found that in a relationship with high levels of trust, gratitude is less likely to be elicited because in such a relationship, both parties take the help for granted. Therefore, it is within the beneficiary's anticipation and less likely to surpass expectations when a benefit is conferred, so the beneficiary feels less grateful.…”
Section: •Expectation Viewpointmentioning
confidence: 99%
“…The relationship between the benefactor and the beneficiary has influence over gratitude. Unsworth, Turner, Williams, and Piccin-Houle (2010) found that in a relationship with high levels of trust, gratitude is less likely to be elicited because in such a relationship, both parties take the help for granted. Therefore, it is within the beneficiary's anticipation and less likely to surpass expectations when a benefit is conferred, so the beneficiary feels less grateful.…”
Section: •Expectation Viewpointmentioning
confidence: 99%
“…Thus, gratitude is not easily elicited; Forster, Pedersen, Smith, McCullough, and Lieberman [10] had a similar discussion. In addition, one study indicated that the higher the level of trust in the relationship, the more the help is taken for granted, so that gratitude is less likely to be elicited [11]. This is the case for the relationship between children and their parents.…”
Section: Bartlett and Destenomentioning
confidence: 99%
“…Seguidamente, os estudantes são gratos ao orientador por este ajudá-los a conseguir o título desejado e por meio do amparo nas disciplinas, na dissertação ou na tese e em outras pesquisas. Os pós--graduandos ainda apresentam sentimento de gratidão em relação ao orientador devido ao apoio e ao cuidado oferecido pelos professores e pelo empréstimo de materiais úteis para a execução das pesquisas (Unswortha et al, 2010). Unswortha et al (2010) identificaram que a gratidão expressa pelos estudantes faz com que orientadores se sintam satisfeitos e contentes consigo mesmo, reconhecidos e realizados com o seu trabalho.…”
Section: Fatores Relacionais Da Adaptação à Pós-graduaçãounclassified
“…Os pós--graduandos ainda apresentam sentimento de gratidão em relação ao orientador devido ao apoio e ao cuidado oferecido pelos professores e pelo empréstimo de materiais úteis para a execução das pesquisas (Unswortha et al, 2010). Unswortha et al (2010) identificaram que a gratidão expressa pelos estudantes faz com que orientadores se sintam satisfeitos e contentes consigo mesmo, reconhecidos e realizados com o seu trabalho. Ademais, expressar gratidão melhora a relação de trabalho entre orientadores e orientandos, pois comunica respeito pelo orientador por parte do aluno.…”
Section: Fatores Relacionais Da Adaptação à Pós-graduaçãounclassified
See 1 more Smart Citation